Identifying and analysis the speculative factors affecting land use changes and activity (Case study:Gisha street in Tehran) - Reza kheyroddin; Nazanin Mostafavi Esfahani (تحقیقات کاربردی علوم جغرافیایی)
Landuse planning goals as the main core of urban planning are classified and studied from different aspects. The inclusion of additional value of surplus funds in the city can highlight capital funding. Following this, changes in urban land demand as the spatial changes of activities and functions occur.The commercialization of residential areas and the tendency of residential landuse changes are the disadvantages of these changes,which constitute a major part of residential neighborhoods of Tehran metropolis ,especially the northern neighborhoods of the city. The main structure of Nasr neighborhood in the 2th district of Tehran is based on Gisha street. The most important issue is multiplicity of commercial land uses in the Gisha street. According to the observations there is a bank in every 45metres of the street , while the performance radius of bank activities is defined in the region scale. It is argued that land price growth, financial and speculative justifications of these changes can cause pressure on the environment.Therefore, according to the above mentioned factors,the main objective of this study is identifing the factors affecting landuse changes in the Gisha street. The research method in this study is documentary , local survey as well as the use of factor analysis in order to determine factors affecting landuse changes.By using this method, accessibility,landeconomics and activity distribution and neighborhood structure were considered as three factors affecting land use changes in the Gisha street . Finally, in order to plan to control the speculative consequences of these changes , the analysis of external and internal factors with regard to indicators in questionnaire, SWOT table and finally defensive strategy to offer strategies and policies was adopted these strategies were presented in two categories: sustainable management of income sources of urban management and control of changes in land use changes.